Antithrombotic effect and plasma pharmacochemistry of Justicia Procumbens L - Hui Zhang; Yating Liu; Fengxian Hu; Siyi Chen; Zhoutao Xie; Hezhen Wu; Ting Zhang; Bo Liu (PLoS ONE, 2025)
Importance Justicia procumbens L. contains lignans with remarkable antiplatelet aggregation effects. Its ethyl acetate extract has demonstrated the efficacy of inhibiting platelet aggregation in preliminary tests. Identifying key components, elucidating the antithrombotic mechanism, and evaluating its potential for treating thrombotic diseases are of great significance. Methods Chemical analysis was conducted on the ethyl acetate extract of J. procumbens. Animal models of carotid artery and venous thrombosis, combined with proteomics analysis, were employed to study the antithrombotic mechanism. Results Chemical analysis identified justicidin B (JB) and chinensinaphthol methyl ether (CME) as the major active antithrombotic constituents. The extract inhibited platelet aggregation by regulating relevant signaling pathways, showing potential in preventing both venous and arterial thrombosis. Conclusions This study confirmed that the ethyl acetate extract of J. procumbens, especially the lignan components JB and CME, can effectively inhibit platelet aggregation, showing promising prospects in treating thrombotic diseases. This provides ideas for the development of health products based on J. procumbens and lays a foundation for further clinical exploration.